1978
DOI: 10.1007/bf01935974
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of the platelet aggregating activity of ristocetin A

Abstract: Hydrolysis of ristocetin A in 0.1 N HCl at 37 degrees C for 2 h resulted in the loss of its ability to induce platelet aggregation in platelet-rich plasma derived from guinea-pigs and humans. However its antibiotic activity against Staph. aureus was not lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…162164 Later, studies identified an aspect of the ristocetin structure that could be easily removed through selective enzymatic cleavage of rhamnose, which eliminated the induced platelet aggregation in vivo . 165 …”
Section: Total Synthesis Of Ristocetin a Aglyconmentioning
confidence: 99%
See 1 more Smart Citation
“…162164 Later, studies identified an aspect of the ristocetin structure that could be easily removed through selective enzymatic cleavage of rhamnose, which eliminated the induced platelet aggregation in vivo . 165 …”
Section: Total Synthesis Of Ristocetin a Aglyconmentioning
confidence: 99%
“…Shortly following this initial disclosure, the complex was introduced into the clinic in 1957. Reports of incidents of patient mortality forced this antibiotic to be pulled from the market after two years of clinical use. , A common link was identified where patients missing a platelet factor, those with von Willebrand’s disease, suffered platelet aggregation, attributing to the deaths. As a result, ristocetin A aggregation of patient platelets in drawn blood samples is used today to diagnosis this disease and to detect abnormalities in this protein. Later, studies identified an aspect of the ristocetin structure that could be easily removed through selective enzymatic cleavage of rhamnose, which eliminated the induced platelet aggregation in vivo …”
Section: Total Synthesis Of Ristocetin a Aglyconmentioning
confidence: 99%
“…Isolated from Nocardia lurida and patented for use as an antibacterial by Abbott in 1961, ristocetin A was discontinued in clinical use 2 years after being introduced due to incidences of patient mortality attributable to platelet aggregation . Subsequently, this latter activity was found to be eliminated through enzymatic cleavage of rhamnose from the pendant tetrasaccharide . Currently, ristocetin A is used clinically to diagnose von Willebrand's disease, a common genetic hemorrhagic disorder 11 and has found use as an electrophoretic and chromatographic chiral selector .…”
mentioning
confidence: 99%